Incorporating the Gut Microbiome in the Risk Assessment of Xenobiotics and Identifying Beneficial Components for One Health - Ampatzoglou, Antonis; Gruszecka-Kosowska, Agnieszka; Torres-Sánchez, Alfonso; López-Moreno, Ana; Cerk, Klara; Ortiz, Pilar; Monteoliva-Sánchez, Mercedes; Aguilera, Margarita (Frontiers in Microbiology, 2022)
Three areas of relevance to the gut microbiome in the context of One Health were explored; the incorporation of the microbiome in food safety risk assessment of xenobiotics; the identification and application of beneficial microbial components to various areas under One Health, and; specifically, in the context of antimicrobial resistance. Although challenging, focusing on the microbiota resilience, function and active components are critical for advancing the incorporation of microbiome data in the risk assessment of xenobiotics. Moreover, the human microbiota may be a promising source of beneficial components, with the potential to metabolize xenobiotics. These may have possible applications in various areas, e.g., in animals or plants for detoxification or in the environment for biodegradation. This approach would be of particular interest for antimicrobials, with the potential to ameliorate antimicrobial resistance development. Finally, the concept of resistance to xenobiotics in the context of the gut microbiome may deserve further investigation.